Student indebtedness amongst graduates from Canadian Optometry Schools - Bitton, Etty; Jones, Deborah (Canadian Journal of Optometry, 2009)
Purpose: The objective of this study was to investigate the level of student indebtedness amongst the graduates from the two Canadian optometry schools (Montreal and Waterloo). A secondary objective was to investigate the financial impact of the clinical externship program on the overall student debt. Methods: The 2007 graduating class was surveyed anonymously. Information was obtained on demographics, number of years of study, expenses related to externships and the overall estimated level of debt upon graduation. Results: The mean overall debt varied between zero and one hundred and fifty thousand (150,000 Cdn), with UW students having a higher mean debt (UM 26,750; UW 75,165 Cdn; p<0.05). Males had a significantly higher debt than females at either school (F 48,200 vs M 59,231; p<0.05). Conclusions: This is the first report of Canadian optometry student indebtedness. Understanding the factors that contribute to the optometry student indebtedness is the first step in understanding the financial burden of students attending Canadian optometry schools.